Fuzzy Graphs - Al Mutab, Huda Mutab (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper, neighbourly irregular fuzzy graphs, neighbourly total irregular fuzzy graphs, highly irregular fuzzy graphs and highly total irregular fuzzy graphs are introduced. A necessary and suﬃcient condition under which neighbourly irregular and highly irregular fuzzy graphs are equivalent is provided. We deﬁne d2 degree of a vertex in fuzzy graphs and total d2 -degree of a vertex in fuzzy graphs and (2, k)-regular fuzzy graphs, totally (2, k)- regular fuzzy graphs are introduced. (2, k)- regular fuzzy graphs and totally (2, k)-regular fuzzy graphs are compared through various examples.